Al-Warraqa and the Warraqoon and Their Scientific Role in Educational Institutions in Iraq during the 3rd and 4th Islamic Centuries / 9th and 10th Centuries AD - Hassan, Dr. Qader Mohammed Hassan; Abdel-Sahib, Dr. Hadeel Saadoun Abdel-Sahib (Sulaimani Journal for Humanities, 2026)
During the 3rd and 4th Islamic centuries (9th and 10th centuries AD), the profession of Al-Warraqa (scribes and copyists) and the Warraqoon (scribes) played a significant role in the intellectual and cultural life of Iraq, especially within educational institutions. The Warraqah profession was closely linked to the documentation and transmission of knowledge and contributed significantly to the preservation of scientific heritage. This profession primarily involved the manual copying of books and manuscripts. In this era, the activities of the Warraqoon included several key functions: · Book copying: Transcribing religious, scientific, and literary texts by hand. · Text verification: Reviewing and carefully copying texts to ensure the accuracy and preservation of information. · Manuscript preparation: Decorating books and adding explanations and footnotes. Educational institutions in Iraq during this period consisted mainly of mosques and Warraq shops, which focused on jurisprudential and intellectual studies. Libraries, especially in Baghdad and other Iraqi cities, served as major centers for knowledge exchange. This study is divided into two main sections. The first section examines the emergence of the Warraq profession during the Abbasid era, focusing on its social foundations within Iraqi society, particularly in Baghdad. The second section explores the role of the Warraqoon in scientific life, especially inside institutions that formed the solid scientific nucleus of the era. This includes the scientific contributions of the Warraqoon within mosques and their shops and stalls.
Keywords: booksellers; booksellers; educational institutions; Iraqi society